Statistics and common sense - Nobuyuki Hanaki; Jan R. Magnus; Donghoon Yoo (Tinbergen Institute, 2021)
Common sense is a dynamic concept and it is natural that our (statistical) common sense lags behind the development of statistical science. What is not so easy to understand is why common sense lags behind as much as it does. We conduct a survey among Japanese students and try to understand why some probabilistic and statistical questions that baffled great minds a few hundred years are now easy, while other (relatively straightforward) questions are not only difficult but even counter-intuitive.
Keywords: B16; C10; C91; D80; D90; 330; probability; statistical methods; experiment; common knowledge